A Critical Autobiography of Moral Learning across Four Generations of the Woman’s Christian Temperance Union: A Feminist Genealogy - Dorothy Agnes Lander (Adult Education Research Conference, 2000)
This qualitative evaluation of the intergenerational moral learning related to the activist work of the Woman’s Christian Temperance Union (WCTU) constitutes a critical re-membering of growing up in a WCTU home and community. I trace the public and private continuities and discontinuities of moral learning across four generations of Ontario WCTU families in the 20th century.